PENGARUH METODE SOSIODRAMA TERHADAP KEMAMPUAN MENENTUKAN UNSUR INTRINSIK CERPEN SISWA KELAS V SD NEGERI 131 PEKANBARU - Ella Miranda (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2019)
The background of this study is the lack of student attention to learning material. This study aims to describe the influence and differences in the ability to determine the intrinsic elements of students' short stories using the sociodrama method. This research was conducted in class V SD Negeri 131 Pekanbaru. Based on the results of the study it was found that there is an influence of the ability to determine the intrinsic element in the experimental class as seen from the average of the initial test and the final test, namely the initial test of 60.63 to 81.88 when the final test with a large influence of 56%. In the final test of the control class and the experimental class obtained t_count = 21,708 ≥ t_table = 1,999, so there is a difference in the ability to determine the intrinsic element between the control class and the experimental class. So, there is an influence (experimental class) and differences in abilities (between the control class and the experimental class) fifth grade students of SD Negeri 131 Pekanbaru